Molecular validation of genetically transformed Catharanthus roseus plants via different strains of Agrobacterium tumefaciens - Rania El-Tanbouly; Hend Hassan; Lojina M. Awd; Azza Ali Makhlouf; Hani G. Shalabi; Sarah El-Messeiry (Heliyon)
Medical plants play a crucial role in the pharmaceutical industry due to their natural synthesis of active compounds. Synthetic methods exist, which provide fewer effective molecules compared to those naturally occurring. Catharanthus roseus, a significant medicinal plant, synthesizes vital vinca alkaloids and various secondary metabolites widely used in cancer and hypertension treatment. However, genetic modification using Agrobacterium tumefaciens-mediated transformation, a common method for altering periwinkle plants, suffers from low efficiency and reproducibility. Factors like the Agrobacterium strain can influence transformation efficiency and post-transformation regeneration. This study compares the transformation and regeneration efficiency of three A. tumefaciens strains (LBA4404, EHA105, and GV3101) carrying the GUS gene and kanamycin selection via syringe infiltration in Catharanthus roseus. Molecular variations between mutants were examined using Inter-Simple Sequence Repeat (ISSR) and GUS expression via quantitative Real-Time PCR (qRT-PCR). Results revealed that GV3101 had the highest transformation efficiency (61.1 %) and LBA4404 the lowest (38 %). However, GV3101-infected explants had the lowest regeneration rate (10 %), the obtained mutants from it exhibited the highest GUS expression. ISSR analysis indicated 37 % polymorphism among mutants, highlighting the impact of Agrobacterium strains on plant genetics and potentially on phytochemical compositions. Overall, this study recommends using GV3101 for high transformation efficiency and LBA4404 for superior in vitro regeneration in Catharanthus roseus, suggesting a promising method for efficient gene transformation in this plant species.